1986
DOI: 10.1097/00000658-198603000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Giant Gastric Ulcers

Abstract: Traditional therapy for giant gastric ulcers (greater than 3 cm) has been gastric resection because of a presumed high risk of hemorrhage and recurrence. To determine the validity of this approach and decide whether the need for resection has been altered by the introduction of H2-blockers, the records of 10,054 gastroduodenal endoscopies performed between 1971 and 1984 were reviewed. Forty-nine patients with giant gastric ulcers were identified. Five patients had malignant ulcers. Ten patients underwent gastr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

1987
1987
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 8 publications
0
6
1
Order By: Relevance
“…Lastly, the proportion of giant ulcers found at autopsy among non-surgically treated subjects who died of ulcer disease was greater than the percentage among subjects operated on during life, suggesting perhaps that the giant ulcers more often led to death. Thus, giant ulcers in this series, in contrast to those studied by Barragry et al [13], still seemed to represent a severe form of ulcer disease.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Lastly, the proportion of giant ulcers found at autopsy among non-surgically treated subjects who died of ulcer disease was greater than the percentage among subjects operated on during life, suggesting perhaps that the giant ulcers more often led to death. Thus, giant ulcers in this series, in contrast to those studied by Barragry et al [13], still seemed to represent a severe form of ulcer disease.…”
Section: Discussioncontrasting
confidence: 69%
“…Among these recent cases, only 3 patients, or 6% of all those undergoing surgery for giant ulcers, had actually been on such therapy. Nonetheless, others have reported that giant ulcers respond promptly to medical treatment [13][14][15][16], and they should be so treated, provided no complications of the ulcer are present. If, however, ulcer healing is delayed, the increased risk of life-threatening bleeding from an unhealed giant ulcer clearly adds to the indications for operation.…”
Section: Discussionmentioning
confidence: 99%
“…Giant gastric ulcer (GGU) has been defined as an ulcer >3 cm in diameter or large enough to occupy at least one wall [1, 2]. The incidence of GGU in the pre-H2 receptor antagonist (H2RA) era varied between 12 and 24% of all gastric ulcers [2, 3].…”
Section: Discussionmentioning
confidence: 99%
“…We have found lesions where radiology examination was suggestive o a gastric diverticulum or a gastric fundus tumoral process (Figures 3 and 4). We hav found such ulcers after immunosuppressant therapies with mycophenolate-mofeti administered post-heart transplant [10][11][12][13][14].…”
Section: Giant Ulcers (Over 2-3 Cm)mentioning
confidence: 91%